Kendala Komunikasi Dalam Pembelajaran Daring di Wilayah Pedesaan Selama Wabah Covid-19. - Hernaningtyas, Anisa (Jurnal Representamen, 2022)
This study was conducted intending to get a reflection of the communication barriers or obstacles experienced by teachers and students in the online learning system during the Covid-19 pandemic. The methods imposed in this study are case studies that are qualitatively descriptive, there is also data obtained consisting of primary and secondary data. Primary data is obtained from interview methods and dialogues with informants, while secondary data is obtained from various library sources related to all information related to online learning. Based on the results of the research of obstacles that found, namely, obstacles or technical pests, then there are simantic obstacles, and the last is behavioral barriers, which have an impact on the difficulty of students to follow and understand and master learning materials well.